2019
DOI: 10.1515/cog-2018-0063
|View full text |Cite
|
Sign up to set email alerts
|

Smoothly moving through Mental Spaces: Linguistic patterns of viewpoint transfer in news narratives

Abstract: This article presents a Mental Space model for analyzing linguistic patterns in news narratives. The model was applied in a corpus study categorizing various linguistic markers of viewpoint transfers between the mental spaces that readers must conceptualize while processing news narratives: a Reality Space representing the journalist and reader’s projected here-and-now viewpoint; a News Narrative Space representing the newsworthy events from a there-and-then viewpoint; and an Intermediate Space representing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Clients' conceptualization of ideas while communicating through a narrative deploys certain linguistic forms, reflecting cognitively-based language discipline. Their linguistic forms provide cues to the therapists on how the clients construct the intended Gilles Fauconnier's 'Mental Space' model such as BASE SPACE, PARENT SPACE, CHILD SPACE (Fauconnier, 1994(Fauconnier, , 1997Fauconnier & Turner, 2002), REFLECTION SPACE (Evans & Green, 2006;Fauconnier, 1994), REALITY SPACE (Al Masudi & Daghir, 2017;Fauconnier, 1994;Krieken, 2016;Van Krieken & Sanders, 2019), DEPICTION SPACE (Evans & Green, 2006;Mok et al, 2004), DESIRE SPACE (Fauconnier, 1994;Hamad et al, 2018) and POSSIBILITY SPACE (Evans & Green, 2006).…”
Section: Throughoutmentioning
confidence: 99%
See 1 more Smart Citation
“…Clients' conceptualization of ideas while communicating through a narrative deploys certain linguistic forms, reflecting cognitively-based language discipline. Their linguistic forms provide cues to the therapists on how the clients construct the intended Gilles Fauconnier's 'Mental Space' model such as BASE SPACE, PARENT SPACE, CHILD SPACE (Fauconnier, 1994(Fauconnier, , 1997Fauconnier & Turner, 2002), REFLECTION SPACE (Evans & Green, 2006;Fauconnier, 1994), REALITY SPACE (Al Masudi & Daghir, 2017;Fauconnier, 1994;Krieken, 2016;Van Krieken & Sanders, 2019), DEPICTION SPACE (Evans & Green, 2006;Mok et al, 2004), DESIRE SPACE (Fauconnier, 1994;Hamad et al, 2018) and POSSIBILITY SPACE (Evans & Green, 2006).…”
Section: Throughoutmentioning
confidence: 99%
“…The verbalization shows that language behaviours play a noteworthy role in the clients' reflection journey on art psychotherapy. Clients' feedback during Reflect Interview provides insights into the conceptualization of abstract ideas while processing a narrative about their journey in art psychotherapy (Cienki, 2013;Van Krieken & Sanders, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies found that even implicit representation of news characters' viewpoints enhances the news texts' attractiveness (Sanders & Redeker, 1993). To reconstruct what took place within news sources' consciousness at the time of the news events is a complex cognitive task for both journalist and the audience (Van Krieken & Sanders, 2019a). It requires journalists to give a voice to their sources or to mix their voice with the sources' voice, and to represent this using subjective literary techniques, such as direct free indirect speech and thought.…”
Section: Literary Techniques In Journalismmentioning
confidence: 99%
“…Seit der Jahrtausendwende hat das Interesse an Narrativität wieder zugenommen, insbesondere unter dem Stichwort ›Storytelling‹, unter dem insbesondere die deutlich dramatisierende und emotionalisierende Rekonstruktion von Ereignissen in der Berichterstattung verstanden wird (vgl. Shim 2014 ; Krieken 2016 ).…”
Section: Die Welt Erzählen: News Narrativesunclassified